Estimates of heritabilities and genetic correlations in polled Hereford cattle selected for feed conversion - J.B. Jr. Glaze; R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1999)
Performance records of 1459 Polled Hereford cattle were analyzed to estimate heritabilities and genetic correlations of beef cattle traits from birth to maturity. Estimates of heritability (h2) for birth weight (BWT), weaning weight (WWT), yearling weight (YWT), scrotal circumference (SC), yearling height (YHT), mature height (MHT), and mature weight (MWT) were moderate to high, with the exception of WWT (h2 = .14), and ranged from .38 to .72. The traits associated with feed conversion, daily feed intake (INT), average daily gain (ADG), and feed conversion (CONV) had heritabilities of .24, .25, and .14, respectively. Genetic correlations (rg) between the growth traits (BWT, WWT, YWT, YHT, MHT, MWT, and SC) were positive and ranged from .20 to .88. The rg=.99 between milk production (MILK) and maternal weaning weight (MWW) indicates that the traits are essentially the same and supports the method in which many breed associations calculate and report expected progeny differences (EPDs) for milk production. The rg = .42 between ADG and INT, rg = .27 between INT and CONV, and the rg = -.82 between ADG and CONV suggest that faster gaining cattle have greater feed intakes and are more efficient.
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Selection; Feed conversion; Growth traits; Heritability; Genetic correlation; Polled Hereford